Resilient selves: A theology of resonance and secularity. Issue 2 (28th May 2020) - Gregersen, Niels Henrik
Abstract: This essay contrasts two visions of selfhood: the buffered, autonomous self, and the flexible, resonant self. The autonomous self, while robustly assertive and active, seeks to insulate itself from threats, thereby robbing it of vital connections to other selves and to nature. The resonant self, in contrast, risks more by standing in fluid relationships of resonance and dissonance with its social and natural environments. While the two stand in tension, a baptismal theology entails both elements of a sheltered self and a resonant self that remains flexible and responsive to the ups and downs of human experience. Conversely, even a secular‐minded person will have access to important zones of resonance.